The effect of training on employee performance in Lahat district hotels - Tambunan, Sontina Griche; Sihombing, Daniel; Rizkina, Seila (Trigin Publisher, 2024)
This research aims to determine the effect of training on employee performance in Lahat Regency Hotels. The data analysis method used in this research is a quantitative descriptive method. The population in this study were 38 hotel employees in the 2 and 3 star Lahat Regency. In this research, the data collection method used is a questionnaire while the analysis technique used in this research is simple regression. Based on the research results, training has an effect on employee performance variables. This is indicated by the value of Alpha = 0.05, so the value obtained is Sig = 0.000 < Alpha = 0.05. The results of the coefficient of determination test (R2) obtained an R Square value of 0.247, meaning that the remuneration variable explains the employee performance variable by 24.7%.